1999
DOI: 10.1046/j.1365-2249.1999.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of killer inhibitory receptors on cytotoxic cells from HIV-1-infected individuals

Abstract: Dysfunction of cytotoxic activity of T and natural killer (NK) lymphocytes is a main immunological feature in patients with AIDS, but its basis are not well understood. It has been recently described that T and NK cell-mediated cytotoxicity can be regulated by HLA killer inhibitory receptors (KIR). In this work, we have determined on cytotoxic T cells and NK cells from HIV-1-infected individuals the expression of the following KIR molecules: p58, p70, and ILT2 (immunoglobulin-like family KIR) as well as CD94 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 33 publications
3
49
2
1
Order By: Relevance
“…A number of studies have shown that KIRs are expressed by memory/effector CTL under conditions of chronic Ag stimulation, such as tumors and HIV infection, leading to the view that the NK-IRs perhaps serve to reduce CTL-mediated immunopathology after protracted antigenic stimulation (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Although these studies authenticate that CTL can express NK-IRs under certain situations, their role in a primary immune response in vivo was not clear.…”
mentioning
confidence: 99%
“…A number of studies have shown that KIRs are expressed by memory/effector CTL under conditions of chronic Ag stimulation, such as tumors and HIV infection, leading to the view that the NK-IRs perhaps serve to reduce CTL-mediated immunopathology after protracted antigenic stimulation (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Although these studies authenticate that CTL can express NK-IRs under certain situations, their role in a primary immune response in vivo was not clear.…”
mentioning
confidence: 99%
“…In addition, numerous regulatory proteins have been reported to induce on T cells during chronic HIV-1 and biologically affect T cell function [36][37][38]. Here, no difference of expression of a panel of T-cell exhaustion and activation-related genes (PD-1, CTLA-4, KLRG1, GRAIL, Itch and Cbl-b) was observed for these TCR-clonotypic clones, indicating that these regulatory proteins did not account for the differential antiviral efficacy of these clones.…”
Section: Discussionmentioning
confidence: 99%
“…Study of Tarazona et al (2002) [45] observed an increase of CD56-CD94+ cells in HIV+ patients, corroborating studies that reinforce the increasing of the CD56neg population in these patients. Study of Galiani et al (1999) [46] observed an increase of NK and T cells expressing CD94. The same author describes a possible association between IL-10 and CD94 expression in these cells.…”
Section: Changes In Cd94+ Populationsmentioning
confidence: 99%